Sex steroid hormone function in the brain niche: Implications for brain metastatic colonization and progression - Contreras‐Zárate, María J. (Cancer Rep (Hoboken), 2020)
BACKGROUND: While sex hormones and their receptors play well‐known roles in progression of primary tumors through direct action on sex steroid hormone‐responsive cancer cells, emerging evidence suggest that hormones also play important roles in metastatic progression by modulating the tumor microenvironment. Estrogens and androgens synthesized in gonads and within the brain influence memory, behavior, and outcomes of brain pathologies. Yet, their impact on brain metastatic colonization and progression is just beginning to be explored. RECENT FINDINGS: Estradiol and testosterone cross the blood‐brain barrier and are synthesized de novo in astrocytes and other cells within the adult brain. Circulating and brain‐synthesized estrogens have been shown to promote brain metastatic colonization of tumors lacking estrogen receptors (ERs), through mechanisms involving the upregulation of growth factors and neurotrophins in ER+ reactive astrocytes. In this review, we discuss additional mechanisms by which hormones may influence brain metastases, through modulation of brain endothelial cells, astrocytes, and microglia. CONCLUSION: A greater understanding of hormone‐brain‐tumor interactions may shed further light on the mechanisms underlying the adaptation of cancer cells to the brain niche, and provide therapeutic alternatives modulating the brain metastatic niche.